Intact Goal-Driven Attentional Capture in Autistic Adults. Issue 1 (26th March 2021) - Husain, Layal; Berggren, Nick; Remington, Anna; Forster, Sophie
Background: Autistic individuals have been found to show increased distractibility by salient irrelevant information, yet reduced distractibility by information of personal motivational salience. Here we tested whether these prior discrepancies reflect differences in the automatic guidance of attention by top-down goals. Methods: Autistic (self-reported diagnoses, confirmed with scores on the Social Responsiveness Scale) and non-autistic adults, without intellectual disability (IQ > 80 on Wechsler Abbreviated Scale of Intelligence), searched for a color-defined target object (e.g., red) among irrelevant color objects. Spatially uninformative cues, matching either the target color or a nontarget/irrelevant color, were presented prior to each display. Results: Replicating previous work, only target color cues reliably captured attention, delaying responses when invalidly versus validly predicting target location. Crucially, this capture was robust for both autistic and neurotypical participants, as confirmed by Bayesian analysis. Limitations: While well powered for our research questions, our sample size precluded investigation of the automatic guidance of attention in a diverse group of autistic people (e.g. those with a range of cognitive abilities). Conclusions: Our findings imply that key mechanisms underlying the automatic implementation of top-down attentional goals are intact in autism, challenging theories of reduced top-down control.